Feasibility Study of Drainage System Outline Plan in Curup District, Rejang lebong Regency - Prayitno, Ragil Adi; Belladona, Meilani; Wardhani, Fenty Wisnu (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2023)
The purpose of this study is to determine the feasibility of the drainage system outline plan based on the Regulation of the Minister of Public Works and Public Housing (PUPR) number 14 of 2018 in Rejang Lebong Regency, especially in Curup District. Based on the results of the feasibility test analysis of the drainage system outline plan in Curup District, it was found that the condition of the drainage system was categorized as feasible. Waterlogging that often occurs due to closed drainage channels and buried in soil. Then, in the category of infrastructure and wastewater treatment facilities are declared infeasible because based on the outline conditions the capacity of drainage channels amounting to 0.0417186 m3 / s cannot accommodate dirty / waste discharge originating from population activities, which is 56,442,2006 m3/sec.